2008
DOI: 10.1143/jjap.47.5763
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ge Switch in Phase Transition: Approach using Atomically Controlled GeTe/Sb2Te3 Superlattice

Abstract: Germanium-antimony-tellurite (GST) is a very attractive material not only for rewritable optical media but also for realizing solid state devices. Recently, the study of the switching mechanism between the amorphous and crystal states has actively been carried out experimentally and theoretically. Now, the role of the flip-flop transition of a Ge atom in a distorted simplecubic unit cell is the center of discussion. Turning our viewpoint towards a much wider region beyond a unit cell, we can understand that Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 14 publications
(13 reference statements)
3
60
0
Order By: Relevance
“…The annealing of the as-grown GeTe/ Sb 2 Te 3 SL films at 503 K ͑230°C͒ for 10 min changed the amorphous states into the crystalline state. 19 The TEM measurements confirmed that the GeTe/ Sb 2 Te 3 SLs have layered structures with clear interfaces. In addition, the structural change of the GeTe/ Sb 2 Te 3 SLs was evident from the increase in the reflectivity ͑ϳ10%͒ after the annealing.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The annealing of the as-grown GeTe/ Sb 2 Te 3 SL films at 503 K ͑230°C͒ for 10 min changed the amorphous states into the crystalline state. 19 The TEM measurements confirmed that the GeTe/ Sb 2 Te 3 SLs have layered structures with clear interfaces. In addition, the structural change of the GeTe/ Sb 2 Te 3 SLs was evident from the increase in the reflectivity ͑ϳ10%͒ after the annealing.…”
mentioning
confidence: 66%
“…Our motivation for the use of the atomically controlled GeTe/ Sb 2 Te 3 SLs is based on the new structural model that Ge 2 Sb 2 Te 5 is considered as superlattice, which consists of two units: one is a Ge 2 Te 2 layer and the other is a Sb 2 Te 3 layer. 19,20 That indicates understanding the role of the flipflop transition of the Ge atom in the distorted simple-cubic unit cell will be a promising strategy toward the reversible transition by means of the irradiation of ultrashort laser pulses. Our experiments show that the frequency of the coherent A 1 optical modes decreases with increasing the lattice temperature.…”
mentioning
confidence: 99%
“…The sample investigated was [GeTe/Sb 2 Te 3 ] 20 consists of alternatively deposited 5 nm thick GeTe sublayers and 5 nm thick Sb 2 Te 3 sublayers, which has been described in detail elsewhere [10]. Time-resolved pump-probe reflectivity measurements were performed utilizing a near--infrared optical pulse with 20 fs duration with a wavelength of 850 nm generated by a Ti:sapphire laser oscillator.…”
Section: Methodsmentioning
confidence: 99%
“…Chong et al reported that phase-change electrical memory based upon superlattice (SL)-like (GeTe)/ (Sb 2 Te 3 ) provided better performance with respect to the switching speed and programing current as well as durability [9]. Subsequently, crystallographically strongly--oriented GST-SL with superlattice wavelengths only a few monolayers thick were developed [10] based on the phase-change model of Kolobov and workers [11] and were shown to greatly reduce the energy requirements for switching due to a reduction in dimensionality. Furthermore, some of the current authors demonstrated ultrafast phase change from the disordered to crystalline phases within 1 ps by manipulation of the local vibrational modes originating from local GeTe 4 units in GST--SL [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation